2018
DOI: 10.15406/ipmrj.2018.03.00160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prurıtus on qualıty of lıfe in patıents wıth tinea

Abstract: Purpose: The aim of this study was to determine descriptively the impact of pruritus on quality of life in patients with tinea pedis. Methods:The study included 214 patients referring to dermatology outpatient clinic at Kayseri Research and Teaching Hospital between May 2016 and August 2016 with diagnosis of tinea pedis and meeting the inclusion criteria. Study data was collected by face to face interview with patients via survey form and Dermatological Quality of Life Index (DLQI) and Modified Pruritus Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…29 A study in Turkey that looked at the impact of itch in patients with athlete's foot, reported QoL to be negatively affected with increasing level and severity of itch. 30 Itching (with burning) can get aggravated by sweating, heat, hot water and after disrobing (atmokinesis), and can disturb sleep in many patients. Nocturnal exacerbation of pruritus is common.…”
Section: Sfi and Its Impact On Quality Of Life (Qol)mentioning
confidence: 99%
“…29 A study in Turkey that looked at the impact of itch in patients with athlete's foot, reported QoL to be negatively affected with increasing level and severity of itch. 30 Itching (with burning) can get aggravated by sweating, heat, hot water and after disrobing (atmokinesis), and can disturb sleep in many patients. Nocturnal exacerbation of pruritus is common.…”
Section: Sfi and Its Impact On Quality Of Life (Qol)mentioning
confidence: 99%